Changes in arthropod family richness, activity-density, biomass and body-size differed along a grazing intensity gradient: Modulation of plant traits and soil moisture conditions - Wang, Yadong; Li, Yanlong; Shi, Chunjun; Cheng, Jianwei; Zhang, Jialu; Wang, Yanan; Guo, Jingpeng; Liu, Xinmin; Li, Frank Yonghong (Journal of environmental management, 2025)
Arthropods play a critical role in the functioning of grassland ecosystems, and are largely affected by herbivore grazing. However, the mechanisms of grazing affecting arthropod community, especially through modulating plant traits and soil properties, are still unclear. We investigated the variation in arthropod community variables including family richness, activity-density, biomass, and body size in typical steppe grasslands subject to grazing at four intensity levels (nil, light, moderate and heavy) in central Inner Mongolia (China), and analyzed the relationships of these variations with grazing-induced changes in plant traits, plant community attributes and soil properties. We found that (i) at the community level, arthropod family richness was lower in moderately-grazed than in both lightly- and heavily-grazed grasslands, but no significant difference was detected between grazing and no-grazing grasslands. The high arthropod community activity-density was found in plant communities with high plant leaf nitrogen content and low water content. (ii) With increasing grazing intensity, the biomass of arthropod community decreased, while the proportion of small-sized arthropods increased, and the family composition, especially the families of Coleoptera changed. (iii) The response of arthropods to grazing intensity differed among arthropod orders. The family richness of Coleoptera, Diptera and Homoptera increased with the increase of plant leaf water content and C:N ratio or the decrease of leaf nitrogen content; Orthoptera activity-density declined with increasing grazing intensity, but showed no significant correlation with plant leaf traits, community attributes, or soil water content; Hymenoptera activity-density declined with the increase of plant height, biomass and cover, and the decrease of plant individual density and family richness; a greater Lepidoptera activity-density was found in the grassland with high vegetation cover and moist soil; and Diptera exhibited larger biomass and body size in grasslands with increased plant nitrogen content. (iv) Depending on grazing conditions, some arthropod families may alter their feeding preferences and select more stable environmental conditions for survival, potentially weakening the inherent relationship between arthropods and plants. Our study implies it is necessary to incorporate the dynamics of ground arthropods into the grassland management for conservation and sustainable use of grassland ecosystems. •Variations in arthropod and plant communities were analyzed in grazing grasslands.•Arthropod family richness was lower under moderate grazing intensity.•Arthropods, especially Coleoptera, miniaturized with grazing intensity increase.•Response of arthropods to grazing intensity differed among arthropod orders.•Grazing may potentially weaken the intrinsic arthropod-plant relations.